Consumers, Are You Ready to Accept Blockchain Technology in Purchasing Food? - Helen WONG; Carmen SUM; Hau-ling CHAN (Communications of International Proceedings, 2020)
Manufacturers and retailers of the food industry in Hong Kong are adapting their businesses to the disrupted market triggered by the coronavirus pandemic, social and political issues, economic recession, and trade tensions. The adoption of blockchain technology is revealed as a breakthrough to transform the food industry for serving the market with new consumption behaviours and adjusted supply-chain practice. Industry giants like Nestlé and Walmart are utilising the blockchain technology to improve business performance, while consumers’ acceptance of using the blockchain-enabled application in purchasing food is not yet known. This conceptual paper aims to explore literature and propose a conceptual model related to consumers’ acceptance of blockchain-enabled applications in purchasing food to address this research gap. Combining the technology acceptance model (TAM) and the unified theory of acceptance and use of technology (UTAUT), social influence and self-efficacy are proposed to determine consumers’ intention to use the blockchain application with perceived usefulness and perceived ease of use as the intermediating variables.
Keywords: blockchain; food market; TAM; UTAUT